Impact of different antiseptics on umbilical cord colonization and cord separation time - TOPUZOĞLU, AHMET; ÖZEK, EREN; BİLGEN, HÜLYA SELVA; ÖZDEMİR, HÜLYA (J INFECTION DEVELOPING COUNTRIES, 2017)
Introduction: There is still some uncertainty on cord care practices all around the world, especially in developing countries. The aim of our study was to investigate the effects of six different umbilical cord care practices on the rate of colonization and cord separation time. Methodology: A total of 516 newborns were randomly allocated to the following six umbilical cord care groups: group 1 received dry care; groups 2-4 received a single application of 70% alcohol, 4% chlorhexidine, or povidon-iodine in the delivery room, respectively, which were discontinued thereafter; groups 5 and 6 received a single application of 70% alcohol or 4% chlorhexidine, respectively, starting in the delivery room and continuing every six hours until discharge. Umbilical cords were examined on the second and third days and between the fifth and seventh day for signs of omphalitis. Swab cultures were taken on the second or third day from all cases. Results: Cord separation time (median [interquartile range]) was the shortest for group 1 (7 [6-7] days) and the longest for group 3 (10 [7-12] days) and group 6 (10 [8-12] days) (p < 0.001). The cord colonization in the swab cultures was significantly lower in groups 3 and 6 (p < 0.001). Omphalitis was detected in eight (1.5%) patients among the study population, and there was no significant difference between the groups. Conclusions: Our study showed that chlorhexidine application was the most effective agent in decreasing colonization, though it increased cord separation time significantly in both groups.
Keywords: newborn; cord care; colonization; cord separation time; omphalitis; BACTERIAL-COLONIZATION; NEONATAL-MORTALITY; OMPHALITIS; CHLORHEXIDINE; PREVENTION; INFECTION; CARE; PAKISTAN